Double asymmetric hydrogenation of conjugated dienes: a self-breeding chirality route for C2 symmetric 1, 4-diols. Issue 6 (20th December 2018) - León, Félix; Francos, Javier; López-Serrano, Joaquín; García-Garrido, Sergio E.; Cadierno, Victorio; Pizzano, Antonio
Abstract : Asymmetric hydrogenation of1 is performed with good enantio- and diastereoselectivity with Rh-Duphos/BPE catalysts providing a self-breeding chirality process. Abstract : The synthesis and double asymmetric hydrogenation of ( Z, Z )-1, 3-diene-1, 4-diyl diacetates is described. In this reaction C 2 / meso ratios up to 85 : 15 and enantioselectivities up to 97% ee have been achieved. As the hydrogenation products can be converted into chiral 1, 4-diols, key starting materials for the preparation of the best catalysts used, this catalytic system enables a self-breeding chirality process.